A Comprehensive Review on Qualitty Assessment and Mangement of Water - Gehlot, Vijay Singh; Kachhawha, Suresh; Gehlot, Tarun; Khan, Aman; Tudawat, Atul (Journal of Neonatal Surgery, 2025)
The most significant factor in forming the terrain and controlling the climate is water. It is among the most significant substances that have a significant impact on life. The physical, chemical, and biological properties of water are typically used to characterize its quality. Water quality is declining and aquatic biota is being depleted as a result of extensive and diverse contamination in aquatic environments brought on by rapid industrialization and the careless use of chemical pesticides and fertilizers in agriculture. Water-borne illnesses affect the human population as a result of drinking tainted water. As a result, it is essential to periodically check the water quality. Temperature, pH, turbidity, salinity, nitrates, and phosphates are among the parameters that may be measured. Water quality may also be determined by evaluating the aquatic macroinvertebrates. This paper reviews the assessment methods and management for quality of water.